Case report: Metastatic BRAF V600E–mutated adult Wilms’ tumor with robust response to BRAF/MEK inhibitor therapy - Kroll, Matthew R.; Au, Cherry; Slostad, Jessica; Christ, Trevor N.; Papas, Sam G.; Tan, Alan (Frontiers in Oncology, 2024)
Nephroblastoma or Wilms’ tumor (WT), is the most common pediatric renal malignancy but rare in adults. Treatment protocols for adults are typically extrapolated from pediatric guidelines, but there are no standard guidelines for adults due to the rarity of the disease. However, next-generation sequencing (NGS) has led to new therapeutic options for adult WT patients. We present the first case to our knowledge of a recurrent adult Wilms’ tumor treated with dual-BRAF/MEK targeted therapy, which showed initial robust clinical response and was well-tolerated.